Architekturbasierte Bewertung und Planung von Änderungsanfragen (2017)
Software Architecture covers the technical organization of a software system and principles which determine design and evolution of the system. The research issue of this work results from software evolution, when the software needs to be modified. The contribution of this book is a method for change request analysis based on software architecture models. The method supports derivation of tasks covering several work areas and life cycle phases.